Association of air pollutants, airborne occupational exposures, and chronic rhinosinusitis disease severity. Issue 2 (29th October 2019) - Velasquez, Nathalia; Moore, John A.; Boudreau, Robert M.; Mady, Leila J.; Lee, Stella E.
Abstract : Background: Previous work has shown that chronic rhinosinusitis (CRS) severity may be associated with particulate matter 2.5 (PM2.5 ) and black carbon (BC) in CRS patients without nasal polyps (CRSsNP). Data regarding occupational exposures, however, are lacking. We assessed the impact of PM2.5, BC, as well as occupational airborne exposure on CRS disease severity. Methods: Patients with CRS with nasal polyps (CRSwNP), CRSsNP, and aspirin‐exacerbated respiratory disease (AERD) were identified from an institutionwide database. Spatial modeling from 37 pollutant monitoring sites in Allegheny County was used to estimate exposures. Patient occupations using the 2010 Standard Occupation Classification (SOC10) and airborne occupation exposures to vapors, gases, dusts, fumes, fibers and mists (VGDFFiM) or diesel fumes were recorded. Disease severity was measured by modified Lund‐Mackay score (LMS), systemic corticosteroid therapy, and incidence of functional endoscopic sinus surgery (FESS). Results: Two hundred thirty‐four patients were included (CRSwNP, n = 113; CRSsNP, n = 96; AERD, n = 25). The prevalence of AERD among those with CRSwNP was 18%. Patients exposed to VGDFFiM or diesel fumes required higher steroid doses vs nonexposed patients ( p = 0.015 and p = 0.03, respectively); patients with VGDFFiM levels >5% were more likely to undergo FESS vs nonexposed patients ( p = 0.0378). There was no difference in PM2.5 and BC with regard to disease severity and FESS between CRSwNP, CRSsNP, and AERD patients. Steroid use was significantly higher in CRSwNP and AERD vs CRSsNP ( p = 0.001). LMS was significantly higher in AERD as compared with CRSwNP and CRSsNP ( p = 0.001). Conclusion: Occupational airborne exposure to VGDFFiM correlated with increased prevalence of FESS and need for corticosteroids in CRS patients. There was no difference in PM2.5 and BC levels and disease severity outcome measures between CRS subtypes in this subset.